Finite Element Simulation and Analysis of Femoral Head Replacement - Asgari, Seyed Alireza (2003)
Although several years of research and experiment are dedicated to Total Hip Replacement (THR) of the conventional implant, there is yet no reliable answer for those patients who are very active and young. In this study, a modelling of the bone around two different types of implant has been carried out. Currently proposed design studied here, is the generic concept of stemless implant. The stemless implant reconstruction was compared to the conventional implant and also to the intact bone as control solution. A modelling approach with Finite Element (FE) method was adopted. A model of femur was developed and element optimisation was carried out to find the best mesh refinement. The models were divided into two regions from proximal head to 40 mm distance toward distal end (R1) and 40 mm distance from proximal head toward the distal end (R2). For two different loading conditions of bending and torsion, the models were solved by ANSYS software. The results were compared with those of the experimental literature for validation. The results of this study showed that the stem less implant had less deviation from the control sol ution of the bone in a l l reg ions and in both loading cond itions, com pa ring to the large d eviation of the stemmed i mplant fro m the intact bone. The stemless i mplant showed perfect fit to the control sol ution i n R2 region except for the 14 m m highest part of this reg ion where the ste m le ss i mplant showed strain red uction in the i nterface of the bone and the implant. This region wa s sub-trochanter and wa s concluded to practically be the weak point of this type of implant. Meanwhile, the stemless i mplant type had sign ificant changes in stress and strain d i stribution i n R1 reg io n . This region was the im plant region itself and it was concluded that a g reat amount of care m u st be taken for this region when designing such an i m plant. The results of this study ind icated that the stem less type of i m p lant could become a suitable alternative fo r conve ntional type of implant in hemia rthroplasties. However, the fixation of this type of i mplant and its effect on subtrochanter region m u st be con sidered for d esigning the fi nal prod uct. More comprehensive numerical investigations on specific designs, with more loading cond itions and contact algorithms inclusion, could be of major benefit to improve the fi nal o utcome of the design process.